Experimental performance of concrete-encased CFST columns subjected to full-range fire including heating and cooling. (15th June 2018) - Zhou, Kan; Han, Lin-Hai
Highlights: Experiments of concrete-encased CFST columns under the combined effect of fire and loading. Finite element analysis (FEA) model to calculate the temperature distribution of concrete-encased CFST column. Simple calculation method of calculating the fire resistance and post-fire residual strength of concrete-encased CFST column. Abstract: Concrete-encased CFST (concrete-filled steel tube) columns are gaining popularity in constructions especially in high-rise buildings and large-span structures. This type of composite column features an inner CFST component and an outer reinforced concrete component. Extensive literature is available on the structural performance of concrete-encased CFST columns at ambient temperature, however, the fire performance of this type of composite columns has seldom been addressed. To fill in this research gap, this paper thus experimentally studies the performance of concrete-encased CFST columns subjected to full-range fire including heating and cooling. A set of tests, including six fire resistance tests and four postfire tests, respectively, were conducted under the combined effect of load and fire. Test observations and results are presented, including fire resistance, postfire residual strength, failure modes, temperature versus time relationships and deformation versus time relationships. The fire performance of concrete-encased CFST columns is analysed and discussed based on these observations. It is found that due to the insulating effect of the outer reinforced concrete, concrete-encased CFST columns exhibits higher fire resistance in fire and higher postfire residual strength as compared with conventional CFST columns without concrete encasement. The simple calculation model of analysing the fire resistance of composite column in Eurocode 4 was extended and then employed to calculate the fire resistance as well as the postfire residual strength of concrete-encased CFST columns. The predictions are found to be conservative as compared with test data, and this simplified method are applicable to assess the fire resistance and postfire residual strength of concrete-encased CFST columns.